Marketing Strategy In Increasing Revenue Restaurant Business from Islamic Economic Perspective - Annisa Rustiani; Chairunnisa Nasution; Erpina Manurung; Achmad Zulfikar Siregar (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2022)
Marketing strategy is a strategy to serve a market or market segment that is targeted by an entrepreneur. Therefore, the marketing strategy is a combination of the marketing mix implemented by entrepreneurs to serve their market. Based on the formulation of the problem, this study aims to determine the marketing strategy of food stall entrepreneurs in increasing the income of the food stall business. The type of research used in this study is empirical, because in this study the researcher describes a situation or phenomenon from the research object studied by developing concepts and gathering existing facts. This research method is descriptive qualitative. From the research results, the marketing strategy used to increase entrepreneur income is by implementing a marketing mix system; product, price, place and promotion. Viewed from an Islamic economic perspective, food stall entrepreneurs also apply the practices of the Prophet Muhammad SAW, namely shiddiq (true and honest), amanah (trustworthy), fathanah (smart), and tabligh (communicative).